Diseño y construcción de un deshidratador experimental de hierbas aromáticas y condimentales, por convección forzada de aire con quemador de GLP. - Zaruma Macas, Jorge Gustavo (2014)
In the present report the steps are detailed and developed through of the design and construction of an experimental dehydrator of flavor aromatic herbs and was developed by forced air convection burner LPG in order to improve the quality of dehydrated products Dehydrator trays were selected with a heat exchanger cross flow and once done the calculations and set the temperature of 400C for the dehydrator, it was proceeded to the construction of the camera dehydrated with stainless steel plate 304, which has the internal dimensions of 90cm x 70cm x 50cm, so the external dimensions were as follows: 101.5cm x 84cm x 0.64 cm, considering the space for media trays and folds of stainless steel plates. The insulating selected for the chamber dehydrated is the glass wool which is applied to a thickness of 6.5 cm on the vertical walls and door, while in the bottom wall of glass wool was applied in a thickness of 7.5cm and the top wall glass wool was applied in a thickness of 4 cm. For construction exchanger calculations an array of 26 tubes 40 cm, Cell 40 ASTM A53 GRB, nominal 1 "diameter, which were placed in a staggered, but to complete the arrangement was put 28 tubes, which were obtained by leaving the accordance with the following dimensions 47cm x 22cm x 40 Consequently burner LPG commercial 12 KW is selected, the document also contains recommendations for the design, construction, operation and maintenance of equipment.